Magneto-optical Kerr effect investigation on magnetoelectric coupling in ferromagnetic/antiferroelectric multilayer thin film structures - Mirshekarloo, Meysam Sharifzadeh (2013)
Magnetoelectric (ME) membranes comprising soft ferromagnetic Ni and antiferroelectric (AFE) (Pb,La)(Zr,Sn,Ti)O3 (PLZST) layers were proposed and fabricated through a bulk micro-machining process on silicon wafers. An AC-mode magneto-optical Kerr effect technique was proposed to examine the magnetoelectric coupling in the multilayer membranes, in which the electric field-induced magnetization rotation was analyzed for understanding the underlying coupling mechanisms. The AFE to ferroelectric phase transformation of PLZST induced a rotation of magnetization of about 0.5° in Ni, persuaded by strain-induced anisotropy of about −0.5 kJ/m3.